MENINGKATKAN PENGUASAAN KOSAKATA MELALUI FINDING WORDS GAME SISWA KELAS DELAPAN DI SMPN 1 SUMBERGEMPOL TULUNGAGUNG TAHUN AKADEMIK 2015/2016 - Purwasih, Galuh Dwi (Jurnal al Hikmah, 2016)
This study design using Action Research (PTK), so the researchers are using Actional hypothesis. The hypothesis of this study can be stated as follows: